Spectroscopic insights exploring triacylglyceride accumulation in Scenedesmus sp. via biomolecular transitions. (December 2020) - Anand, Vishal; Kashyap, Mrinal; Ghosh, Atreyee; Kiran, Bala
Abstract: In current study, microalgae Scenedesmus sp. was treated with three different salts with varying levels from 10 to 100 mM: Sodium chloride (NaCl), Magnesium chloride hexahydrate (MgCl2 .6H2 O) and Calcium chloride dihydrate (CaCl2 .2H2 O). NaCl (100 mM) treated cells showed highest lipid accumulation in comparison to other salts. On the other hand, little improvement in lipid accumulation was also observed with varying concentrations of CaCl2 .2H2 O and MgCl2 .6H2 O. Further, Fourier Transform Infra-Red (FTIR) spectroscopy reveals biomolecular transitions leading to changes in Triacylglycerides (TAGs) and hydrocarbon (CH) stretches from the lipids. It is observed that the maximum TAG was accumulated when treated with NaCl (70 mM). This was further confirmed through the ratio of TAGs to Amide and CH to Amide. Thus, in relevance to rapid analysis of algal samples for lipid accumulation and changes in biomolecular transitions of proteins and carbohydrates with salt treatment, FTIR can direct us to a noninvasive approach. Graphical abstract: Unlabelled Image Highlights: Impact of different salt on Scenedesmus sp. was monitored for triacylglycerides accumulation. FTIR spectroscopy reveals changes in TAGs and hydrocarbons stretches from the lipids in Scenedesmus sp. exposed to stress. TAGs to Amide and Hydrocarbon (CH) to Amide ratio further confirmed the data. FTIR is a noninvasive analysis technique, which is used in the present study to investigate the accumulation of TAGs.